Evaluating the mitigation effectiveness of forests managed for conservation versus commodity production using an Australian example. Issue 4 (24th February 2022) - Keith, Heather; Mackey, Brendan; Kun, Zoltan; Mikoláš, Martin; Svitok, Marek; Svoboda, Miroslav
Abstract: Forests are critical for biodiversity conservation and climate change mitigation: reducing emissions, increasing removals, and providing resilient ecosystems with stable long‐term carbon storage. However, evaluating the mitigation effectiveness of forests managed for conservation versus commodity production has been long debated. We assessed factors influencing evaluation of mitigation effectiveness––land area, time horizon, reference level, carbon stock longevity––and tested the outcomes using analyses of carbon dynamics from an Australian ecosystem. Results showed that landscape scale accounting using carbon carrying capacity as the reference level and assessed over a series of time horizons best enables explicit evaluation of mitigation benefits. Time horizons need to differentiate between near‐term emissions reduction targets (2030 and 2050), relative longevity of carbon stocks in different reservoirs, and long‐term impacts on atmospheric CO2 concentration. Greatest mitigation benefits derive from conservation through continued forest growth (52% gain in carbon stock by 2050) and accumulating carbon to attain carbon retention potential (70% gain). Cumulative emissions from harvesting result in permanent elevation of atmospheric CO2 concentration (32 times the annual emission by rotation end). We recommend these time horizons and landscape scales for evaluating forest management to better guide policies and investments for achieving climate mitigation and biodiversity conservation.